Step-count guidelines referenced on 60-minutes of moderate/vigorous physical activity - Fontana,Fabio Eduardo (2015)
The purpose of this study was to establish step-count guidelines for sixth-grade students and assess the ability of step-counts to discriminate between students achieving and not achieving 60-minutes of moderate to vigorous physical activity daily. 201 sixth-grade students completed the study. They wore a pedometer and an accelerometer at the waist level for one full day. ROC curves were used to establish step-count guidelines and determine the diagnostic accuracy of step-counts. Sixth grade students need 12,118 steps/day to reach adequate daily levels of physical activity. The AUC indicated good diagnostic accuracy of step-counts. Suggested step-count guidelines can be a useful tool for identifying children who need to increase their daily levels of physical activity. The step-count cutoff proposed in this study is adequate for discriminating between sixth grade students reaching and not reaching recommended levels of physical activity.